Liberia : Poverty Reduction Strategy Paper: Second Annual Progress Report, 2009-10. (IMF Staff Country Reports; Country Report ;, 2011)
Poverty has been a major challenge for Liberia. All developmental, governance, and social indicators have shown improvement as a result of a more robust implementation strategy led by the government with the support of development partners, civil society, and the private sector. The general economic condition has improved. However, enormous challenges remain for crafting of the next development strategy to fill any potential gap in development planning, the mobilizing and strategically placing of the private sector at the heart of economic growth and job creation.